Gingival Overgrowth as a complication of kidney transplantation – Nepali perspective - Thapa, Swosti; Basnet, Robin Bahadur; Shrestha, Bikal; Thakur, Amresh; Shrestha, Neesha; Shrestha, Anup Lal; Basnet, Nabin Bahadur (Nepalese Medical Journal, 2019)
Gingival Overgrowth is a known and common complication with multifactorial etiology seen in kidney transplant recipients. Gingival Overgrowth is induced in kidney transplant recipients by Cyclosporin A and Calcium Channel Blockers that are frequently prescribed to them as immunosuppressive and antihypertensive, respectively. There have been 1477 kidney transplantations in Nepal since the first kidney transplantation in 2008, but cases of gingival Overgrowth have not been reported in any publications. The aim of this review is to discuss the different aspects of gingival Overgrowth and its relevance to kidney transplant recipients of Nepal. This review will emphasize the need to examine the oral cavity of kidney transplant recipients. Genetic predisposition, oral health, and offending drugs are involved in the pathogenesis of gingival Overgrowth. This review discusses the pathogenesis, clinical features, and management aspects of gingival Overgrowth in kidney transplantation recipients. The reason for gingival Overgrowth not being reported in Nepal could be due to various reasons like favorable genes, good oral hygiene, or avoidance of drugs that cause gingival Overgrowth in kidney transplantation recipients. This could also be due to gingival Overgrowth being ignored by the patients and the treating doctors. These aspects are reviewed with reference to previous publications.